Method for producing superabsorbent particles
The method stabilizes the operation of vibratory conveyor belts by using a guiding device and stripping mechanism to prevent polymer gel adherence, ensuring consistent operation and efficiency in producing superabsorbent particles.
Patent Information
- Application Number
- JP2021542341
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-01-23
- Filing Date
- 2020-01-13
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-01-13
AI Technical Summary
Existing methods for producing superabsorbent particles face challenges in maintaining stable operation of vibratory conveyor belts due to polymer gel adherence, leading to belt misalignment and reduced drive force.
A method involving the use of a vibrating conveyor belt with a guiding device at its end to uniformly coat polymer gel, combined with a stripping device to prevent gel adherence and misalignment, ensuring consistent operation.
Prevents polymer gel from slipping under the conveyor belt, maintaining belt alignment and drive force, thereby enhancing the stability and efficiency of the production process.
Smart Images

Figure 0007621259000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing superabsorbent particles by polymerizing a monomer solution or suspension, comprising the steps of drying the obtained aqueous polymer gel in an air circulation belt dryer, grinding, classifying and optionally thermal surface postcrosslinking, wherein the aqueous polymer gel is introduced into the air circulation belt dryer by a vibrating conveyor belt and a guide device is located at the end of the conveyor belt. [Background technology]
[0002] Superabsorbents are used to manufacture diapers, tampons, sanitary napkins and other hygiene articles, but are also used as water retention agents in commercial horticulture. Superabsorbents are also called water-absorbing polymers.
[0003] The production of superabsorbents is described in the article "Modern Superabsorbent Polymer Technology", FL Buchholz and AT Graham, Wiley-VCH, 1998, pp. 71-103.
[0004] Performance characteristics, e.g. 49.2g / cm 2 To improve the gel bed permeability (GBP) and absorbency under a pressure of 0.7 psi (AUL), superabsorbent particles are generally surface postcrosslinked. This increases the level of crosslinking at the particle surface, which is 49.2 g / cm 2 The absorption rate under a pressure of (AUL 0.7 psi) and the centrifugal retention capacity (CRC) can be at least partially separated. This surface postcrosslinking can be carried out in an aqueous gel phase. However, preferably, the dried, ground and sieved polymer particles (base polymer) are surface-coated with a surface postcrosslinking agent and thermally surface postcrosslinked. Crosslinking agents suitable for this purpose are compounds capable of forming covalent bonds with at least two carboxylic acid groups of the polymer particles.
[0005] WO2008 / 087114 A1, WO2010 / 139680 A2 and EP2 700 667 A1 describe the loading of an aqueous polymer gel onto the conveying belt of an air circulating belt dryer by means of a vibrating conveyor belt. Summary of the Invention [Problem to be solved by the invention]
[0006] The object of the present invention was to provide an improved method for producing superabsorbents, in particular a more stable operation of the vibrating conveyor belts used. [Means for solving the problem]
[0007] The purpose of this is to a) at least one ethylenically unsaturated monomer having an acid group, which is at least partially neutralized; b) at least one crosslinker, and c) at least one initiator 1. A method for producing a superabsorbent by polymerizing a monomer solution or monomer suspension comprising: The method includes the steps of drying the obtained aqueous polymer gel in an air circulation belt dryer, grinding, classifying, and optionally thermal surface post-crosslinking, wherein the aqueous polymer gel is introduced into the air circulation belt dryer by a vibrating conveyor belt, and the induction device (1) is located at the end of the conveyor belt (2); This was achieved by the method.
[0008] The vibrating conveyor belt is a conveyor belt that can be periodically swiveled on a vertical axis. The conveyor belt of the vibrating conveyor belt itself runs at an essentially constant speed. The conveyor belt of the vibrating conveyor belt has a significantly smaller width than the conveyor belt of the air circulation belt dryer. The periodic swiveling movement of the vibrating conveyor belt ensures that the conveyor belt of the air circulation belt dryer is homogeneously coated with polymer gel over its entire width. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 shows an embodiment of the invention with a guide device (1), a conveyor belt (2) and a drive / deflection drum (3). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] In a preferred embodiment of the present invention, the induction device (1) is arranged at the discharge end of the conveyor belt, and the length of the induction device (1) is preferably 5% to 70%, more preferably 10% to 50%, and most preferably 15% to 30% of the length of the conveyor belt, the length of the conveyor belt being the distance of the pivot axis from the discharge end.
[0011] The height of the induction device (1) is preferably 5 to 30 cm, more preferably 8 to 25 cm, and most preferably 10 to 20 cm.
[0012] The length and height of the induction device (1) are, for example, 5% to 70% and 5 to 30 cm, 5% to 70% and 8 to 25 cm, 5 to 70% and 10 to 20 cm, 10% to 50% and 5 to 30 cm, 10% to 50% and 8 to 25 cm, 10% to 50% and 10 to 20 cm, 15% to 30% and 5 to 30 cm, 15% to 30% and 8 to 25 cm, or 15% to 30% and 10 to 20 cm.
[0013] The guiding device (1) may be rotated towards the center of the conveyor belt in the running direction by an angle α perpendicular to the running direction of the conveyor belt, the guiding device (1) being preferably rotated by 3° to 15°, more preferably by 6° to 12°, and most preferably by 8° to 10°.
[0014] The part of the guide (1) in contact with the conveyor belt should not be too hard. Suitable materials are natural or synthetic rubber, such as silicone rubber, polyetheretherketone (PEEK), halogenated polyolefins, such as polyvinyl chloride (PVC) or polytetrafluoroethylene (PTFE), polyamide (PA), polypropylene (PP), or polyethylene (PE). Silicone rubber is preferred.
[0015] The guide device (1) preferably follows the curvature of the conveyor belt. The preferred guide device is at the shortest possible distance from the conveyor belt. If the distance is too long, the polymer gel will move outwards between the guide device (1) and the conveyor belt. If the distance is too short, friction, i.e. undesirable mechanical loads, will occur between the guide device (1) and the conveyor belt.
[0016] If the material of the inductor (1) in contact with the conveyor belt is flexible enough, the inductor (1) can even be placed directly on the conveyor belt. In fact, it is possible for the flexible material of the inductor (1), e.g. silicone rubber, placed on the conveyor belt to bend inwards, i.e. towards the polymer gel being transported.
[0017] The guide device (1) preferably projects beyond the discharge end of the conveyor belt. The preferred guide device (1) here follows a downward curvature at the deflection drum (3). The area of the guide device (1) projecting beyond the discharge end of the conveyor belt is preferably parallel to the running direction of the conveyor belt.
[0018] The invention is based on the finding that polymer gel can get under the conveyor belt. This polymer gel then gets on the drum surface of the driving drum or deflecting drum. The polymer gel causes slippage of the belt on the drum surface, which means that the circular conveyor belt on the drum moves to the side. Moreover, the polymer gel on the surface of the driving drum causes the drum to slip, i.e. a reduction in the driving force. The guide device (1) prevents the polymer gel from getting under the conveyor belt. Slippage and slippage of the belt on the driving drum are thereby prevented.
[0019] In a preferred embodiment of the invention, the bottom surface of the return conveyor belt is further cleaned of adhering polymer gel by at least one stripping device.
[0020] The bottom surface of the return conveyor belt is the outside of the conveyor belt, which receives an additional metered amount of polymer gel after turning, and the top surface of the return conveyor belt is the inside of the conveyor belt, which does not come into contact with the polymer gel.
[0021] The distance of the stripping device from the discharge end of the conveyor belt is preferably less than 20% of the length of the conveyor belt, more preferably less than 10% of the length of the conveyor belt, and most preferably less than 5% of the length of the conveyor belt, the length of the conveyor belt being the distance of the pivot axis from the discharge end.
[0022] The stripping device is not subject to any limitations. For example, a brush arranged transversely to the running direction is suitable. Another possibility is the use of a scraper. The scraper is a stripping device arranged transversely to the conveying direction and made of a non-flexible material. An example of a suitable non-flexible material is polytetrafluoroethylene. To prevent damage to the conveyor belt, the scraper should have little or no direct contact with the conveyor belt. The scraper should be inclined with respect to the running direction of the return conveyor belt. This promotes the release of the adhering polymer gel and prevents clogging between the conveyor belt and the scraper. The peeled off polymer gel typically falls onto the conveyor belt of the air circulation belt dryer.
[0023] The scraper is preferably inclined at an angle of 5° to 45°, more preferably 10° to 35°, and most preferably 15° to 25° with respect to a plane perpendicular to the running direction of the conveyor belt. The distance of the scraper to the underside of the return conveyor belt is preferably 0.1 to 5 mm, more preferably 0.2 to 2 mm, and most preferably 0.5 to 1.5 mm.
[0024] The conveyor belt preferably has a length of 2 to 10 m, more preferably 2.5 to 8 m, and most preferably 3 to 6 m, the length of the conveyor belt being the distance of the pivot from the discharge end.
[0025] The conveyor belt preferably has a width of 0.5 to 1.5 m, more preferably 0.6 to 1.2 m, most preferably 0.7 to 0.9 m.
[0026] The speed of the conveyor belt is preferably 0.2 to 2.0 m / sec, more preferably 0.3 to 1.5 m / sec, and most preferably 0.4 to 1.0 m / sec.
[0027] It is possible to use conveyor belts that are customary for this purpose. The surface of the conveyor belt, i.e. the side that will come into contact with the polymer gel, should be water-repellent and have a water contact angle at 23°C of preferably at least 60°, more preferably at least 80°, most preferably at least 100°. The contact angle is a measure of the wetting behavior and is measured according to DIN 53900.
[0028] The water content of the polymer gel on the conveyor belt is preferably 20-80% by weight, more preferably 30-70% by weight, and most preferably 40-60% by weight.
[0029] The temperature of the polymer gel on the conveyor belt is preferably 60 to 105°C, more preferably 70 to 100°C, and most preferably 80 to 95°C.
[0030] The preparation of the superabsorbent is described in detail below.
[0031] Superabsorbents are produced by polymerizing a monomer solution or suspension and are typically water-soluble.
[0032] The monomers a) are preferably water-soluble, i.e. their solubility in water at 23° C. is typically at least 1 g / 100 g water, preferably at least 5 g / 100 g water, more preferably at least 25 g / 100 g water and most preferably at least 35 g / 100 g water.
[0033] Suitable monomers a) are, for example, ethylenically unsaturated carboxylic acids, such as acrylic acid, methacrylic acid and itaconic acid. Particularly preferred monomers are acrylic acid and methacrylic acid. Very particular preference is given to acrylic acid.
[0034] Monomer a) typically comprises a polymerization inhibitor, preferably a hydroquinone monoether, as a storage stabilizer.
[0035] Suitable crosslinking agents b) are compounds that have at least two groups suitable for crosslinking.Such groups are, for example, ethylenically unsaturated groups that can be free-radical polymerized into polymer chains, and functional groups that can form covalent bonds with the acid groups of monomer a).In addition, polyvalent metal salts that can form coordinate bonds with at least two acid groups of monomer a) are also suitable as crosslinking agents b).
[0036] The crosslinker b) is preferably a compound having at least two polymerizable groups which can be subjected to free-radically polymerization into a polymer network. Preferred crosslinkers b) are, for example, ethylene glycol dimethacrylate, diethylene glycol diacrylate, polyethylene glycol diacrylate, allyl methacrylate, trimethylolpropane triacrylate, triallylamine, tetraallylammonium chloride, tetraallyloxyethane, as described in EP 0530438 A1; di- and triacrylates, as described in EP 0547847 A1, EP 0559476 A1, EP 0632068 A1, WO 93 / 21237 A1, WO 03 / 104299 A1, WO 03 / 104300 A1, WO 03 / 104301 A1 and DE 103 31 450 A1; mixed acrylates which contain further ethylenically unsaturated groups in addition to the acrylate groups, as described in DE 103 31 456 A1 and DE 103 55 401 A1. A1; or crosslinker mixtures, as described, for example, in DE 195 43 368 A1, DE 196 46 484 A1, WO 90 / 15830 A1 and WO 02 / 032962 A2.
[0037] The amount of crosslinker b) is in each case calculated on the total amount of monomers a) used, preferably 0.05% to 1.5% by weight, more preferably 0.1% to 1% by weight, most preferably 0.3% to 0.6% by weight. With increasing crosslinker content, the centrifuge retention capacity (CRC) decreases, reaching 21.0 g / cm 2 The absorption rate at a pressure of (AUL 0.3 psi) passes through a maximum value.
[0038] The initiators c) used may be all compounds which generate free radicals under the polymerization conditions, for example thermal initiators, redox initiators or photoinitiators. Suitable redox initiators are sodium peroxodisulfate / ascorbic acid, hydrogen peroxide / ascorbic acid, sodium peroxodisulfate / sodium bisulfite and hydrogen peroxide / sodium bisulfite. Preference is given to using mixtures of thermal initiators and redox initiators, for example sodium peroxodisulfate / hydrogen peroxide / ascorbic acid. The reducing component used is preferably the disodium salt of 2-hydroxy-2-sulfinatoacetic acid; or a mixture of the sodium salt of 2-hydroxy-2-sulfinatoacetic acid, the disodium salt of 2-hydroxy-2-sulfinatoacetic acid and sodium bisulfite. Such mixtures are available as Bruggolite® FF6 and Bruggolite® FF7 (Bruggemann Chemicals, Heilbronn, Germany).
[0039] Typically, an aqueous monomer solution is used. The water content of the monomer solution is preferably 40% to 75% by weight, more preferably 45% to 70% by weight, most preferably 50% to 65% by weight. It is also possible to use a monomer suspension, i.e. a monomer solution with more than the solubility of monomer a), e.g. sodium acrylate. If the water content increases, the energy expenditure in the subsequent drying increases, and if the water content decreases, the heat of polymerization can only be removed insufficiently.
[0040] For optimal function, the preferred polymerization inhibitor requires dissolved oxygen. Therefore, dissolved oxygen can be removed from the monomer solution before polymerization by inerting, i.e., by flowing with an inert gas, preferably nitrogen or carbon dioxide. The oxygen content of the monomer solution is preferably reduced to less than 1 ppm by weight, more preferably to less than 0.5 ppm by weight, and most preferably to 0.1 ppm by weight, before polymerization.
[0041] Suitable reactors for polymerization are, for example, kneading reactors or belt reactors.In kneaders, the polymer gel formed in the polymerization of aqueous monomer solution or suspension is continuously comminuted, for example by contrarotatory stirrer shafts, as described in WO2001 / 038402 A1.Polymerization on belts is described, for example, in DE 3825366 A1 and US 6,241,928.Polymerization in belt reactors forms polymer gel that needs to be comminuted, for example, in extruders or kneaders.
[0042] To improve the drying properties, the comminuted polymer gel obtained by the kneader can be further extruded.
[0043] The acid groups of the resulting polymer gel are typically partially neutralized. Neutralization is preferably carried out at the monomer stage. This is typically achieved by mixing in a neutralizing agent as an aqueous solution or else preferably as a solid. The degree of neutralization is preferably 40-85 mol%, more preferably 50-80 mol%, most preferably 60-75 mol%, for which customary neutralizing agents can be used, preferably alkali metal hydroxides, alkali metal oxides, alkali metal carbonates or alkali metal hydrogen carbonates, as well as mixtures thereof. Instead of the alkali metal salts, it is also possible to use ammonia salts. Particularly preferred alkali metals are sodium and potassium, but very particular preference is given to sodium hydroxide, sodium carbonate or sodium hydrogen carbonate, as well as mixtures thereof. Here, solid carbonates and hydrogen carbonates can also be introduced in encapsulated form, preferably directly into the monomer solution before polymerization, during polymerization or after polymerization and before its drying into the polymer gel. Encapsulation is achieved by coating the surface with an insoluble or only slowly soluble material (e.g., by a film-forming polymer, an inert inorganic material, or a fusible organic material), which retards dissolution and reaction of the solid carbonate or bicarbonate to such an extent that carbon dioxide is not released until during drying and the formed superabsorbent has high internal porosity.
[0044] The polymer gel is then typically dried in an air circulating belt dryer until the residual moisture content is preferably 0.5-10 wt%, more preferably 1-7 wt%, and most preferably 2-5 wt%. This residual moisture content is measured by EDANA Recommended Test Method No. WSP 230.2-05 "Mass Loss Upon Heating". If the residual moisture content is too high, the dried polymer gel will have too low a glass transition temperature T g and further processing is exclusively accompanied by difficulties. If the residual moisture content is too low, the dried polymer gel is too brittle and in the subsequent grinding step, an undesirable large amount of polymer particles with an excessively small particle size ("fines") is obtained. The solid content of the polymer gel before drying is preferably 25% to 90% by weight, more preferably 35% to 70% by weight, most preferably 40% to 60% by weight. The dried polymer gel is then crushed and optionally coarsely ground.
[0045] Thereafter, the dried polymer gel is typically ground and classified, and the equipment used for grinding may typically be a single or multi-stage roll mill, preferably a two or three stage roll mill, a pin mill, a hammer mill or a vibratory mill.
[0046] The average particle size of the polymer particles removed as the product fraction is preferably 150-850 μm, more preferably 250-600 μm, and very particularly 300-500 μm. The average particle size of the product fraction can be measured by EDANA Recommended Test Method No. WSP 220.2 (05) "Particle Size Distribution", where the mass proportions of the sieved fractions are cumulatively plotted and the average particle size is determined graphically. The average particle size, as used herein, is the mesh size value that results in a cumulative 50% by weight.
[0047] To further improve the properties, the polymer particles can be thermally surface crosslinked.Suitable surface crosslinking agents are compounds that contain a group that can form covalent bonds with at least two carboxylic acid groups of the polymer particles.Suitable compounds are, for example, multifunctional amines, multifunctional amidoamines, multifunctional epoxides, as described in EP 0 083 022 A2, EP 0 543 303 A1 and EP 0 937 736 A2, difunctional or multifunctional alcohols, as described in DE 33 14 019 A1, DE 35 23 617 A1 and EP 0 450 922 A2, or β-hydroxyalkylamides, as described in DE 102 04 938 A1 and US 6,239,230.
[0048] The amount of surface postcrosslinker is preferably 0.001% to 2% by weight, more preferably 0.02% to 1% by weight, most preferably 0.05% to 0.2% by weight, in each case based on the polymer particles.
[0049] In a preferred embodiment of the present invention, a multivalent cation is applied to the particle surface in addition to the surface postcrosslinker.
[0050] Polyvalent cations that can be used in the method of the invention are, for example, divalent cations such as zinc, magnesium, calcium and strontium cations, trivalent cations such as aluminum, iron, chromium, rare earth and manganese cations, tetravalent cations such as titanium and zirconium cations. Possible counterions are chloride, bromide, hydroxide, sulfate, hydrogen sulfide, carbonate, hydrogen carbonate, nitrate, phosphate, hydrogen phosphate, dihydrogen phosphate and carboxylate ions such as acetate and lactate. Aluminum hydroxide, sulfate and lactate are preferred.
[0051] The amount of polyvalent cation used is, for example, in each case 0.001% to 1.5% by weight, preferably 0.005% to 1% by weight, more preferably 0.02% to 0.8% by weight, based on the polymer.
[0052] Surface postcrosslinking is typically carried out in such a way that the solution of surface postcrosslinking agent is sprayed onto dry polymer particles. After spray application, the polymer particles coated with surface postcrosslinking agent are surface postcrosslinked and dried, and surface postcrosslinking reaction can occur both before and during drying.
[0053] The spray application of the solution of the surface postcrosslinker is preferably carried out in mixers with moving mixing devices, such as screw mixers, disk mixers and paddle mixers.Particularly preferred are horizontal mixers, such as paddle mixers, and very particularly preferred are vertical mixers.The difference between horizontal mixers and vertical mixers is made by the position of the mixer shaft, i.e. horizontal mixers have a horizontally mounted mixer shaft, and vertical mixers have a vertically mounted mixer shaft.Suitable mixers are, for example, horizontal Pflugschar® plowshare mixers (Gebr. Lodige Maschinenbau GmbH, Paderborn, Germany), Vrieco-Nauta continuous mixer (Hosokawa Micron BV, Doetinchem, Netherlands), Processall Mixmill mixer (Processall Incorporated, Cincinnati, USA) and Schugi Flexomix® (Hosokawa Micron BV, Doetinchem, Netherlands). However, it is also possible to spray the surface postcrosslinker solution in a fluidized bed.
[0054] Surface post-crosslinking agent is typically used in the form of an aqueous solution.The penetration depth of surface post-crosslinking agent into polymer particles can be adjusted via the content of non-aqueous solvent and the total amount of solvent.
[0055] Surface postcrosslinking is preferably carried out in contact dryer, more preferably in paddle dryer, most preferably in disk dryer.Suitable dryers are, for example, Hosokawa Bepex® Horizontal Paddle Dryer (Hosokawa Micron GmbH, Leingarten, Germany), Hosokawa Bepex® Disc Dryer (Hosokawa Micron GmbH, Leingarten, Germany), Holo-Flite® Dryer (Metso Minerals Industries Inc., Danville, USA) and Nara Paddle Dryer (NARA Machinery Europe, Frechen, Germany).In addition, fluidized bed dryer can also be used.
[0056] Surface postcrosslinking can be carried out in the mixer itself by heating the jacket or blowing in warm air.Equally suitable is a downstream dryer, such as a tray dryer, a rotary tube oven or a heatable screw.It is particularly advantageous to carry out mixing and thermal surface postcrosslinking in a fluidized bed dryer.
[0057] The preferred reaction temperature is in the range of 100 to 250° C., preferably 110 to 220° C., more preferably 120 to 210° C., and most preferably 130 to 200° C. The preferred residence time at this temperature is preferably at least 10 minutes, more preferably at least 20 minutes, most preferably at least 30 minutes, and typically up to 60 minutes.
[0058] The surface postcrosslinked polymer particles can then be reclassified and excessively small and / or excessively large polymer particles removed and recycled to the process.
[0059] To further improve properties, the surface postcrosslinked polymer particles can be coated or rewetted.
[0060] The rewetting is preferably carried out at 30-80°C, more preferably 35-70°C, most preferably 40-60°C. At too low temperatures the polymer particles tend to form agglomerates, at higher temperatures the water has already evaporated to a significant extent. The amount of water used for rewetting is preferably 1%-10% by weight, more preferably 2%-8% by weight, most preferably 3%-5% by weight. Rewetting improves the mechanical stability of the polymer particles and weakens their tendency to take up an electrostatic charge. Rewetting is advantageously carried out in a cooler after thermal surface postcrosslinking.
[0061] Suitable coatings for improving the free swelling rate and gel bed permeability (GBP) are, for example, inorganic inert substances such as water-insoluble metal salts, organic polymers, cationic polymers, and divalent or polyvalent metal cations. Suitable coatings for dust binding are, for example, polyols. Suitable coatings for combating the undesirable caking tendency of polymer particles are, for example, fumed silicas such as Aerosil® 200, precipitated silicas such as Sipernat® D17, and surfactants such as Span® 20.
[0062] The present invention further provides a hygiene article comprising a superabsorbent produced by the process of the present invention.
[0063] method The standard test methods referred to hereinafter as "WSP" are described in "Standard Test Methods for the Nonwovens Industry", 2005 Edition, published jointly by international strategic partners EDANA (Herrmann-Debrouxlaan 46, 1160 Oudergem, Belgium, www.edana.org) and INDA (1100 Crescent Green, Suite 115, Cary, North Carolina 27518, USA, www.inda.org), which are available from both EDANA and INDA.
[0064] The measurements should be carried out at an ambient temperature of 23±2° C. and a relative air humidity of 50±10%, unless otherwise stated. The water-absorbing polymer particles are thoroughly mixed prior to this measurement.
[0065] Centrifuge Retention Volume Centrifuge Retention Capacity (CRC) is measured by EDANA Recommended Test Method No. WSP 241.2 (05) "Fluid Retention Capacity in Saline, After Centrifugation".
[0066] Extract amount The extractables content of water-absorbing polymeric particles is determined by EDANA Recommended Test Method No. WSP 270.2 (05) "Extractable". EXAMPLES
[0067] Working Example An acrylic acid / sodium acrylate solution was prepared by successively mixing deionized water, 50% by weight sodium hydroxide solution and acrylic acid, with a degree of neutralization corresponding to 71.3 mol %. The solids content of the monomer solution was 38.8% by weight.
[0068] The polyethylenically unsaturated crosslinker used was polyethylene glycol-400 diacrylate (a diacrylate starting from polyethylene glycol having an average molar mass of 400 g / mol). The amount used was 2 kg of crosslinker per ton of monomer solution.
[0069] To initiate the free radical polymerization, 1.03 kg of a 0.25 wt % aqueous hydrogen peroxide solution, 3.10 kg of a 15 wt % aqueous sodium peroxodisulfate solution, and 1.05 kg of a 1 wt % aqueous ascorbic acid solution were used per ton of monomer solution.
[0070] The throughput of the monomer solution was 20 t / h. The reaction solution had a feed temperature of 23.5° C.
[0071] Each component is divided into 6.3m 3 The following amounts were metered continuously into a List Contikneter continuous kneading reactor (LIST AG, Arisdorf, Switzerland) having a capacity of: 20t / hour of monomer solution 40 kg / hour of Polyethylene Glycol-400 Diacrylate 82.6 kg / h of hydrogen peroxide solution / sodium peroxodisulfate solution 21kg / hour of ascorbic acid solution
[0072] Between the crosslinker addition point and the initiator addition site, the monomer solution was inerted with nitrogen.
[0073] After about 50% of the residence time there was an additional metered addition (1000 kg / h) of fines obtained from the production process by grinding and sieving into the reactor. The residence time of the reaction mixture in the reactor was 15 minutes.
[0074] The resulting aqueous polymer gel was applied to the conveyor belt of an air circulating belt dryer by means of a vibrating conveyor belt.
[0075] The air circulation belt dryer had a length of 48 m. The conveyor belt of the air circulation belt dryer had an effective width of 4.4 m.
[0076] The vibrating conveyor belt had a length of 5 m. The conveyor belt had a width of 0.8 m and an effective width of 0.5 m. The angle of repose of the aqueous polymer gel on the conveyor belt was about 15°. The cross section of the polymer gel bed on the conveyor belt was about 0.04 m. 2 The speed of the conveyor belt was 0.5 m / s.
[0077] Starting from one end position, the vibrating conveyor belt accelerated from a first pivot angle β1 of 13° to an angular velocity of 33° / s, decelerated from a second pivot angle β2 of 20° to an angular velocity of 17° / s, and decelerated from a third pivot angle β3 to the other end position. The total pivot angle was 50°. The double pass (from the first end position to the other end position and back) lasted about 7 seconds. The circulating conveyor belt had a surface of polytetrafluoroethylene (PTFE).
[0078] The temperature of the aqueous polymer gel on the vibrating conveyor belt was 90°C.
[0079] As shown in FIG. 1, at the discharge end of the conveyor belt, a guide device (1) was located at each end of the conveyor belt. The guide devices (1) had a length of about 1200 mm in each case and protruded about 100 mm beyond the discharge end of the conveyor belt. The parts of the guide devices (1) in contact with the conveyor belt were made of silicone rubber and had a thickness of about 5 mm. The guide devices (1) were each rotated toward the center of the conveyor belt in the running direction by about 8.5° perpendicular to the running direction of the conveyor belt. The parts of the guide devices extending beyond the discharge end of the conveyor belt were again parallel to the running direction of the conveyor belt. The guide devices (1) followed the curvature of the deflection rollers (3) until they were vertical, from which they extended directly downwards by about 165 mm.
[0080] A stripping device was located on the bottom side of the vibrating conveyor belt. The stripping device was an elongated scraper mounted transversely to the running direction of the return conveyor belt. The scraper was inclined at 20° to the running direction of the return conveyor belt. The distance of the stripping device from the discharge end was about 5 cm, i.e. the stripping device was located in the area of the deflection roller. The distance of the stripping device to the return conveyor belt was 1 mm. The aqueous polymer gel adhering to the outside of the return conveyor belt is stripped off using the stripping device.
[0081] The operation of the circulating conveyor belt was without problems. The guide device (1) prevented the polymer gel from falling onto the top surface of the return conveyor belt and passing between the drum and the conveyor belt as polymer gel.
[0082] The aqueous polymer gel was dried by continuously flowing the air / gas mixture around the aqueous polymer gel on an air circulating belt dryer, the residence time in the air circulating belt dryer was 37 minutes.
[0083] The dried polymer gel was ground and sieved to a particle size fraction of 150-850 μm.
[0084] The resulting water-absorbing polymer particles had a centrifuge retention capacity (CRC) of 34.9 g / g and an extractables content of 8.5 wt %.
Claims
1. a) at least one ethylenically unsaturated monomer having an acid group, which is at least partially neutralized; b) at least one crosslinker, and c) at least one initiator 1. A method for producing superabsorbent particles by polymerizing a monomer solution or monomer suspension comprising: the aqueous polymer gel obtained by polymerizing the monomer solution or monomer suspension is dried in an air circulating belt dryer, pulverized and classified, the aqueous polymer gel is introduced into the air circulating belt dryer by a vibrating conveyor belt, a guide device (1) is located at the discharge end of the vibrating conveyor belt (2) to prevent the polymer gel from sticking onto the drum surface of the driving drum or deflection drum of the vibrating conveyor belt, the vibrating conveyor belt is a conveyor belt that can be periodically rotated on a vertical axis; method.
2. 2. The method according to claim 1, wherein the length of the guiding device (1) is 15% to 30% of the length of the vibrating conveyor belt, the length of the vibrating conveyor belt being the distance of the pivot from the discharge end, and / or the height of the guiding device (1) is 10 to 20 cm.
3. 3. The method according to claim 1 or 2, wherein the guiding device (1) is rotated towards the center of the vibrating conveyor belt in the running direction by an angle α perpendicular to the running direction of the vibrating conveyor belt.
4. The method according to claim 3, wherein the induction device (1) is rotated by 8° to 10°.
5. 5. The method according to any one of claims 1 to 4, wherein the part of the guide device (1) in contact with the vibrating conveyor belt is made of silicone rubber.
6. 6. The method according to any one of claims 1 to 5, wherein the guiding device (1) follows the curvature of the vibrating conveyor belt.
7. 7. The method according to claim 6, wherein the guide device (1) protrudes beyond the discharge end of the vibrating conveyor belt.
8. 8. The method according to any one of claims 1 to 7, wherein the bottom surface of the return vibrating conveyor belt is cleaned of adhering polymer gel by at least one stripping device.
9. 9. The method of claim 8, wherein the distance of the stripping device from the discharge end of the vibrating conveyor belt is less than 5% of the length of the vibrating conveyor belt, the length of the vibrating conveyor belt being the distance of the pivot from the discharge end.
10. 10. The method according to claim 8 or 9, wherein the stripping device attached to the bottom surface of the return vibrating conveyor belt is a scraper.
11. The method of claim 10, wherein the scraper is inclined at an angle of 15° to 25° relative to a perpendicular to the direction of travel of the vibrating conveyor belt.
12. The method according to claim 10 or 11, wherein the distance of the scraper to the underside of the return vibrating conveyor belt is between 0.1 and 5 mm.
13. 13. The method according to any one of claims 1 to 12, wherein the vibrating conveyor belt has a length of 2 to 10 m, the length of the vibrating conveyor belt being the distance of the pivot from the discharge end.
14. 14. The method according to any one of claims 1 to 13, wherein the surface of the vibrating conveyor belt has a water contact angle of at least 60° at 23°C.
15. 15. The method according to any one of claims 1 to 14, wherein the dried, ground and classified aqueous polymer gel is thermally surface postcrosslinked.
Citation Information
Patent Citations
Cleaner device for conveyor belt
JP2005225587A
Manufacturing of superabsorbent polymers
JP2010515816A
Method for producing superabsorbent polymer particles
JP2012528909A
Alignment device
JP2016078959A
Method for producing water-absorbent polymer particles
JP2017504671A